The Relationship Between Creativity and Attention in Adults. Issue 4 (2nd October 2018) - Carruthers, Lindsey; MacLean, Rory; Willis, Alexandra
Abstract : Creativity is a valuable attribute that involves the generation of original ideas; attention is a vital function that facilitates information selection. There is some evidence that creative people may have poorer attention and are generally more distracted than others, and this distractibility is thought to enable the production of novel ideas. Previous research has largely supported this relationship between creativity and attention, yet they are both multifaceted constructs that can be measured in numerous ways. Using multiple measures of each construct, the aim of this study was to examine which features of creativity and attention might be related in a group of 100 adults (18–80 years, M  = 26.9, SD  = 11.5). Figural divergent-thinking (DT) originality was positively related to self-reported concentration; yet no other relationships were found. Results suggest that there is no consistent relationship between creativity and attention, and past studies that linked creativity to attention, having used just one or two measures, may be premature in their conclusions.